2009
DOI: 10.1038/jcbfm.2009.244
|View full text |Cite
|
Sign up to set email alerts
|

Role of Adenosine A2 Receptors in Regulation of Cerebral Blood Flow during Induced Hypotension

Abstract: The mechanisms responsible for vascular autoregulation in the brain during changes in mean arterial blood pressure are ambiguous. Potentially, adenosine, a purine nucleoside and potent vasodilator, may be involved as earlier studies have documented an increase in brain adenosine concentrations with cerebral ischemia and hypotension. Consequently, we tested the hypothesis that adenosine is involved in vasodilatation during hypotension within the autoregulatory range (>50 mm Hg) by exposing adenosine 2a receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 36 publications
(61 reference statements)
0
34
0
Order By: Relevance
“…23 Although these null mice have been reported to have a normal ratio of ipsilateral-to-contralateral LDF during an H-I insult, 5 it is possible that the absolute level of CBF was reduced in both hemispheres during H-I and recovery because of arterial hypotension and impaired cerebral vasodilation to hypotension and hypoxia with loss of cerebrovascular A 2A receptors. 24 Interestingly, we found that cardiac resuscitation was difficult in piglets treated with SCH 58261 before the induction of H-I. The antagonist likely impaired coronary vasodilation to H-I and thereby could have augmented the ischemic insult to the heart.…”
Section: Discussionmentioning
confidence: 91%
“…23 Although these null mice have been reported to have a normal ratio of ipsilateral-to-contralateral LDF during an H-I insult, 5 it is possible that the absolute level of CBF was reduced in both hemispheres during H-I and recovery because of arterial hypotension and impaired cerebral vasodilation to hypotension and hypoxia with loss of cerebrovascular A 2A receptors. 24 Interestingly, we found that cardiac resuscitation was difficult in piglets treated with SCH 58261 before the induction of H-I. The antagonist likely impaired coronary vasodilation to H-I and thereby could have augmented the ischemic insult to the heart.…”
Section: Discussionmentioning
confidence: 91%
“…There might also be an additional contribution from A 2A R in cells other than neurons or glia: for instance, in the case of ischemic models, there is a contribution of neuronal A 2A R as well as of A 2A R located in peripheral myeloid derived cells [250]. Recent studies also found a striking ability of caffeine to control the integrity and functionality of the blood brain barrier [251,252], which is likely to be an effect operated by the abundant endothelial A 2A R. Finally, given the role of A 2A R in controlling cerebral vessels [253][254][255][256][257][258], it is possible that the A 2A R-mediated vascular control might also contribute to neuroprotection.…”
Section: C Possible Role Of Adenosine a 2a Receptorsmentioning
confidence: 99%
“…Adenosine (ADO) is a cellular metabolite that is formed by the breakdown of intracellular and extracellular adenine nucleotides that are physiologically present at nanomolar concentration inside and outside the cells (Fredholm, 2007). It represents an endogenous modulator of brain functions acting to fine-tune inhibitory and excitatory synaptic transmission (Ribeiro et al, 2010), glial function (Boison et al, 2010), and blood flow (Kusano et al, 2010); moreover, in the nervous system, the level of extracellular ADO rises upon brain damage which follows stroke, ischemia, and epileptic seizures (Ribeiro et al, 2003). Acting through four different G-protein-coupled receptors (A 1 R, A 2A R, A 2B R, and A 3 R), extracellular ADO determines the outcome of different brain injuries, mediating neuroprotective or neurotoxic effects.…”
Section: Introductionmentioning
confidence: 99%